The role of sustainable tourism development in increasing employment rates: An analytical econometric study of a sample of tourism countries for the period (1995-2021). - Sulaiman, Sarah; Mohamed, Reber (Humanities Journal of University of Zakho, 2024)
The study aims to measure the impact of sustainable tourism development on employment rates in several selected tourism countries (Sweden, Switzerland, France, Austria, Italy, Greece, Germany, and Spain) for the period 1995-2021. The goal is to identify the impact and the role of sustainable tourism development on employment in the given countries. The study adopted a quantitative method using an autoregressive model of distributed lags of panel data (Panel_ ARDEL, PMG) to estimate the model parameters for the short and long terms. In the short term, the results showed that there is no statistically significant effect between employment rates and the variables that explain it. However, the estimation results in the long term revealed a positive relationship with a significant impact between the employment rate and foreign direct investment, public spending on education, the industry growth rate, and the growth rate of tourism revenues in the sample countries. In contrast, the variables that had a negative impact were inflation rates, and the population growth rate had a negative but insignificant effect. The study concluded with several proposals, including that tourism development requires focusing on the sustainability of existing tourist facilities instead of increasing the number of tourists. It also suggested that sustainable tourism development is the ideal option for achieving economic and social development. Keywords: sustainable tourism development, employment, Panel-ARDL, tourism revenue growth rate